The Transformation of Turkey's Relations with the Middle East: Illusion or Awakening? - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2012)
In light of recent developments in the Middle East, in particular, the Arab revolts in the first few months of 2011 and the AKP's June 2011 election victory, this article aims to define the changing parameters of Turkey's new Middle Eastern policy under the AKP government, which is based on a new civilizational discourse and a differentiated geopolitical approach. It also discusses the basic dynamics and ideological and doctrinal background of Turkey's new Middle Eastern policy in order to understand the opportunities and constraints of its potential facilitator and conciliator role in the changing political circumstances of the region following the recent Arab uprisings. Despite the limits of Ankara's new civilizational and geopolitical orientation in both discourse and policy, which have at times undermined Turkey's neutrality on intra-Arab or Iranian-Arab axes and its facilitation role between Israel and its regional adversaries, Turkey's new regional posture for the Middle East represents an awakening rather than an illusion.